1999
DOI: 10.1111/j.1474-919x.1999.tb07551.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance off environmental variables in determining the growth off nestling Tree Swallows Tachycineta bicolor

Abstract: Unpredictable, short‐term changes in environmental conditions associated with weather patterns have severe impacts on the reproductive success of Tree Swallows Tachycineta bicolor, as well as other aerial insectivores. We examined the effects of day‐to‐day environmental variation on the growth of nestling Tree Swallows. Using path analysis, we compared the relative importance of changes in food availability, ambient temperature and wind speed on changes in mass and feather length over four years at our study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 59 publications
(43 reference statements)
7
97
3
Order By: Relevance
“…Indeed, McCarty & Winkler (1999) and Bradbury et al . (2003) showed that weather could affect Sky Lark and Yellowhammer nestling development in at least four ways.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, McCarty & Winkler (1999) and Bradbury et al . (2003) showed that weather could affect Sky Lark and Yellowhammer nestling development in at least four ways.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental variation has also been shown to have a significant impact on growth and body size in a range of taxa, mediated by variation in food abundance and availability (bats: Tuttle 1976, Hoying & Kunz 1998carnivores: Russell et al 2002;insectivorous birds: Emlen et al 1991, McCarty & Winkler 1999ungulates: Post et al 1999, Knott et al 2005. In our study, the full-grown mass of foxes was dependent on pre-nutritional independence cub mass and sex, but appeared to be affected to a greater degree by environmentally induced variation in the abundance of an important food resource, earthworms, during the transition to independent foraging.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships between insect abundance and swallow breeding success, especially nestling and postfledgling survival, have been investigated for Tree Swallows (e.g., Quinney et al 1986, McCarty and Winkler 1999a, Nooker et al 2005 and to a lesser extent for other species (e.g., Grüebler and Naef-Daenzer 2008). However, research examining these relationships with multiple species simultaneously has not been conducted.…”
Section: Introductionmentioning
confidence: 99%